The Influence of Skills and Personality Characteristics on Employee Performance at the West Sulawesi Provincial Manpower Office - Musdalifah, Musdalifah; Martini, Andi Indra; Naim, Muh Rezky (Jurnal Economic Resource, 2025)
This study was conducted with the aim of determining the effect of skills and personality characteristics on employee performance at the West Sulawesi Provincial Manpower Office. The research method used was quantitative with primary data collected using questionnaires. The respondents in this study were all civil servants working at the West Sulawesi Provincial Manpower Office, and the sample was selected using purposive sampling. The sample size was determined to be 84 respondents. The formulas used in this study were multiple linear regression, validity test, reliability test, t-test, F-test, and coefficient of determination (R2) test. The results showed that skills had a significant partial effect on employee performance. Personality characteristics also had a significant partial effect on employee performance. Simultaneously, skills and personality characteristics significantly affect employee performance, with a contribution of 42.2%. These findings indicate that although skills and personality characteristics have been proven to contribute to improving employee performance, there are still other factors that also play an important role but have not been revealed in this study.